Currency Crises and Government Finances - Burnside, Craig (World Bank, Washington, DC, 2012)
Fiscal policy plays a big role in currency crises - before, and after they occur. Thus policymakers should not underestimate the importance of fiscal policy: a) the realization of large contingent liabilities can quickly, and dramatically alter government finances, leading to a currency crisis; b) the effects of a currency crisis on government finances depend on the structure of government revenue, spending, and debt; c) the fiscal policies adopted in response to a crisis, influence economic outcomes, especially inflation, and depreciation. The note reviews the traditional models of currency crises, explained as a consequence of unsustainable fiscal policy, and how debt is accumulated, how currency crisis then develops, and why does fiscal policy matter. Focusing on bank bailouts, it is argued that traditional models of currency crises are applicable to emerging markets, suggesting that deficits after the East Asia financial crises could have been anticipated given the region's deteriorating banking systems, but that economic outcomes largely depend on the mix of financing.